Conditions and Opportunities for Overcoming the Economic Crisis - N. I. Komkov (Модернизация, инновация, развитие, 2021)
Purpose: the purpose of the presented article is to study the conditions and possibilities of overcoming the protracted economic crisis in Russia.Methods: the study is based on the use of a modified information logic model, which establishes the relationships between the identified bottlenecks, the causes of their occurrence and possible ways to eliminate these causes.Results: the possibilities of overcoming the crisis are, first of all, to use the potential accumulated in the Russian economy, dispersed by sectors of the complete technological reproduction cycle, including the extraction of resources, their processing into useful materials and semi-finished products, the production of machinery and equipment, as well as the production of final products, the provision of services, infrastructure and waste disposal. Simultaneously with the search for opportunities for economic growth, it is necessary to draw the attention of the Russian Government and the legislative and executive heads to the necessity to correct the strategic mistakes. They were conducted in the process of choosing a resource-export development strategy, separating the financial sector from the support and interests of the development of domestic industrial production sector, ignoring the potential and opportunities for the development of the domestic scientific and technological complex, using imperfect economic management mechanisms, etc. The work justifies the need to overcome a long economic crisis via the management of new opportunities breakthrough, which involves the harmonious development of all economic sectors based on supporting a domestic scientific and technical complex capable to ensure the high technologies development and the competitive products production.Conclusions and Relevance: substantiating and choosing ways to overcome the economic crisis should be focused on achieving harmonious development of all sectors of the economy and using in management practices at the national, corporate and company levels, such methods and instruments of targeted projects and programs management, which are the core basis for economy and society development strategies.